Assets, Activity Choice, and Policy Implications for Social Protection Systems - Gwatinyanya, Godfrey; Yudhistira, Muhammad Halley (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2026)
Research Originality: People in countries like Zimbabwe face ongoing economic challenges, underscoring the importance of improving social protection systems that help households build and own assets. However, there is still a limited understanding of how owning assets affects household economic activities. Without this knowledge, programs may be poorly designed, leading to little improvement in people’s lives and inefficient use of public funds. Research Objectives: This study examines how various livelihood assets affect the participation of urban and rural households in paid employment, non-farm business, and farm business activities in Zimbabwe. Research Method: This paper applies a modified multinomial logistic regression specification on a representative sample of 51,114 observations from the 2012 and 2017 Poverty, Income, Expenditure, and Consumption Survey (PICES) pooled cross-sectional data. Empirical Results: We found a strong association between assets owned and economic activity choices, but with rural-urban differentials. The findings confirm that natural assets such as land and cattle are central to rural livelihoods, and farm business remains the dominant livelihood activity. Secondly, it reveals a critical social or public policy aspect: that education is central to livelihoods in both rural and urban areas, as higher levels of education increase participation in paid employment and non-farm businesses, even across gender. Implications: Zimbabwe would benefit more by boosting social support to cover more secondary and tertiary students, rather than focusing mainly on primary education social grants. JEL Classification: D80, E58, F31